An FCE Corpus-Based Analysis of Writing Errors in Chinese English Learners: Common Types, Patterns, and Pedagogical Implications - Yuanyuan Wu; Xinping Jiao (Journal of English Language Teaching and Linguistics, 2025)
L2 Writing ability is one of the important criteria for measuring the comprehensive ability of English learners. Researchers have gradually deepened their research on writing ability from the study of common error patterns of second language learners. In recent years, it has also shifted to the use of natural language processing technology to achieve automatic error recognition of written texts. However, there are still few studies that conduct systematic and real investigations on the writing errors of specific second language learners, especially Chinese English learners. Therefore, this paper uses the Cambridge Learner Corpus First Certificate in English to study the test scripts produced by Chinese English learners in a real test environment. The study found that Chinese English learners are greatly affected by the negative transfer of their mother tongue, and often make mistakes in tense, subject-verb inconsistency, punctuation, articles, and prepositions. This provides real data presentation for the existing common errors in writing of Chinese English learners. Through the analysis of common error patterns, this study proposes four teaching strategies: establishing a joint classroom of English and Chinese, intensive training on common errors, cultivating awareness of mother tongue interference, and providing personalized feedback, which provides possible research directions and inspirations for existing writing teaching.